Chromium, an essential nutrient and pollutant: a review - Mandina, Shadreck; Mugadza, Tawanda (Midlands State University, 2015)
The increased use of chromium (Cr) in several anthropogenic activities has led to the subsequent soil, surface water and ground water contamination. It has wide applications in the dyes, stainless steel, leather tanning, electroplating of chrome, and wood preservatives industries. Chromium exists in the environment in several diverse forms such as Cr (0), Cr (III) and Cr (VI) species. Cr toxicity depends on its valence state. Cr (VI) which is regarded as being highly mobile is toxic, while Cr (III) is less mobile and less toxic. Cr (VI) being more mobile in soil, more toxic and a stronger oxidant penetrates more readily into the cell membranes than the trivalent form. Chromium does not bioaccumulate in plants and animals therefore high levels of chromium in the environment are highly toxic to plants and animals. Chromium toxicity in human beings is expressed in liver and kidney damage as well as skin lesions or rashes. Symptoms of chromium toxicity in plants include alterations in the seed germination process, reduced growth of roots, stems and leaves, which results in low total dry matter production and yield. This paper reviews properties of trivalent and hexavalent chromium with respect to their essentiality as micronutrients and their toxic harmful effects. Trivalent chromium is essential to normal carbohydrate, lipid and protein metabolism, by making the action of the hormone, insulin, more effective while the hexavalent chromium is toxic and involved in mutagenicity, carcinogenicity, and teratogenicity.